2016
DOI: 10.18805/ijar.8429
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genetic diversity of four quails by microsatellite markers

Abstract: Genetic diversity of four quail populations, including Korean quails (maroon quails), Peking white quails, Chinese yellow quails and Chinese black quails, were analyzed by microsatellite markers, aiming to provide scientific basis for new breeds of Chinese black quails for egg production as well as the assessment, protection and utilization of Chinese quail’s genetic resources. The results showed that 48 alleles were detected by nine microsatellite markers in the four quail populations, with the mean of 5.33 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The 20 microsatellite loci were all highly polymorphic and can be used as effective markers of local Egyptian chicken strains to analyze genetic diversity. Genetically, a microsatellite marker with a PIC>0.7 is considered as an ideal one for genetic studies (Bai et al, 2016). In the present study, some of the selected 20 microsatellite loci showed PIC values of over 0.7, reflecting the possibility of using these loci as candidate genes for the future genetic studies of local Egyptian chicken breeds.…”
Section: Discussionmentioning
confidence: 62%
“…The 20 microsatellite loci were all highly polymorphic and can be used as effective markers of local Egyptian chicken strains to analyze genetic diversity. Genetically, a microsatellite marker with a PIC>0.7 is considered as an ideal one for genetic studies (Bai et al, 2016). In the present study, some of the selected 20 microsatellite loci showed PIC values of over 0.7, reflecting the possibility of using these loci as candidate genes for the future genetic studies of local Egyptian chicken breeds.…”
Section: Discussionmentioning
confidence: 62%
“…Genetic diversity data were analyzed with POPGENE32 (Guo and Elston, 1999;Kavitha et al 2015;Jiménez-Mena et al 2016). Polymorphism information content value (PIC) for all the loci were estimated according to Deshmukh et al (2015) and Bai et al (2016b).…”
Section: Discussionmentioning
confidence: 99%
“…At present, quail breeding is becoming more and more popular in poultry and quail is smaller than other poultry, so quail can be used as a good new experimental animal. Quail can be used as a research animal in many subjects such as poultry reproduction, histology, nutrition, endocrinology, embryology, physiology, pharmacology etc (Zhang et al, 2013;Li et al, 2019, Bai et al, 2016a, 2016b.The experimental values of quail in teaching and scientific studies are increasing gradually (Bai et al,2016c(Bai et al, , 2016d(Bai et al, , 2017. Few studies on correlation analysis between MyoG and carcass characteristics of quail are available.…”
Section: Introductionmentioning
confidence: 99%